Complete Breaker Analysis using Velocity Potential of Linear Wave Theory - Hutahaean, Syawaluddin (International Journal of Advanced Engineering Research and Science, 2019)
In this research, breaker equations were developed to conduct breaker height, breaker depth and breaker length calculations. Wave number conservation equation and mass/energy conservation equation are extracted from velocity potential equation to be used in the formulation of breaker equations. Breaker depth equation is obtained from wave number conservation equation, breaker steepness equation is obtained from kinematic free surface boundary condition and using energy conservation equation of linear wave theory, relation between breaker height and breaker depth is obtained.